Importance of integral motor skills in early education - Lorena Soledad Revilla; Jorge Luis Mina Palacios; Elizeth Mayrene Flores Hinostroza; Derling Jose Mendoza Velazco (Indonesian Institute for Counseling, Education and Theraphy, 2021)
The main objective of this study is to assess the importance of stimulating motor skills at early ages for the integral development of early education students. The study is based on the paradigm of qualitative research of an interpretative nature. For data collection, the technique of theoretical-documentary review was applied. In order to analyze the results, theoretical data were compared with the interpretative qualities of the researchers. As results, it was possible to demonstrate that the current educational model presents traditionalist and academic features that impact and limit possibilities of creativity, dispersion and enjoyment of games of physical-cognitive improvement that are essential in the child stage between three and five (3 and 5) years.